PENGARUH PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT. HOLCIM INDONESIA CABANG PERAWANG KABUPATEN SIAK - Dodi Herdino; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine whether there are positive influence between supervision with Employee Performance At Kutai regency Bappeda office. The population in this study are all Employees who number as many as 20 people, given the relatively small amount taken, this study used census method, the entire population as a respondent. Based on the description above, the analysis tools used in this study is the product moment correlation coefficient. From the calculation results indicate a significant influence of supervision on employee performance in the Office of Regional Development Planning Agency Kutai it is based on the calculation results stating that rhitung greater than rtabel namely 0.982> 0.561 for the critical value of n = 20 the rate significance = 0, 01. For n = 20 then the two variables have a very strong relationship level. After the count r is obtained, then the next authors conducted hypothesis testing using t test of the results of testing this hypothesis, tcount of 22.058 while that for the prices keritis of ttable value is 2,552 which means that the t-test> t table ie 22.058> 2.552 the critical value n -20 with a significance level of 0.01 means that by doing so. It can be said that there is a very strong influence from variable to variable employee performance monitoring in Kutai regency Bappeda office.Keywords: Supervision, Employee Performance